Finding a hippocampal Bayesian estimator for the scaling parameter θ and the reliability function R(t) for the left-truncated Weibull distribution when the shape parameter is known. - ضوية سلمان حسن; بان غانم العاني (Iraqi Journal for Administrative Sciences, 2024)
In this research, the measurement parameter θ and the reliability function R(T) of the left-truncated Weibull distribution were estimated using the hippocampal Bayesian method using the initial distribution of the parameter θ with the class (ML-II-ε) when the shape parameter β is known and under the DeGroot loss function as it is the probability density function. The priors of the base and contaminated distribution are distributed in a frechet distribution with parameters (α0 = 1, σ0) for the original distribution and (α = 1, σ) for the contaminated distribution.